Governing religious diversity in cities: critical perspectives - Martínez-Ariño, Julia (Religion, state & society, 2019)
This collection addresses the question of how cities govern and regulate religious diversity. Its main goals are: 1) to take stock of current research regarding the municipal governance of religious diversity; 2) to put forward new concepts and empirical analyses to enhance this field of study; and 3) to identify potential lines for future enquiry that help move the field forward. The contributions cover a wide variety of topics, such as the roles of laws, state contracts, and urbanism in governing religious diversity, comparisons of diverging governance trajectories in various cities within one country, and the controversies surrounding the celebration of religious events in urban spaces. The contributions also identify factors that influence governance processes at the urban level and their consequences for the practice of religion. The collection covers studies of cities in various European countries as well as in Canada.